Chinese consumers’ apparel purchasing criteria, attitudes, perceived knowledge, face-saving, materialistic and ethical values - Huang, Shuyi (Kansas State University, 2017)
China is the world’s largest apparel producer, exporter, and maintains the largest domestic apparel market. Since economic reform in the 1980s that opened up the Chinese market for foreign investors, China’s domestic apparel market has attracted many foreign (Western) apparel brands (Shenkar, 2005). More than 10,000 different international apparel brands share China’s domestic apparel market, including brands from France, Germany, Italy, Japan, the United States, Britain, and South Korea, among others. Around 2,000 Chinese domestic apparel brands have experienced difficultly surviving in China’s domestic apparel market. Besides the large number of foreign (Western) apparel brands, counterfeit apparel products have grown faster than China’s government can control. As a result, China has become the world’s largest counterfeit market. This has become a secondary threat to China’s domestic apparel market and national economy. Additionally, because of economic growth and modernization in China, Chinese consumers have accepted more Westernized values, but also retained their traditional face-saving values. Therefore, the purpose of this study is to explore how their attitudes toward counterfeit apparel products, China’s domestic apparel brands, and foreign (Western) apparel brands are influenced by their level of perception about knowledge and attitudes toward counterfeit apparel products, face-saving values, materialistic values, and ethical values. This study utilized a sample of males and females between the ages of 18 and 64, who reside in Guangzhou, Shanghai, Chengdu, and Wuhan, China. A questionnaire was utilized as part of this study and data was collected online by SOJUMP Survey Company. A total of 1,192 participants (736 males and 456 females) participated in this study. There are in total nine significant relationships that have been found in this study. First, the researcher found a positive relationship between Chinese consumers’ perception about knowledge of counterfeit apparel products and their attitudes about counterfeit apparel products. Second and third, the present study also discovered that Chinese consumers with favorable attitudes of foreign apparel brands or negative attitude of China’s domestic apparel brands would similarly hold positive attitudes of counterfeit apparel products. Fourth, the present scholar concluded that Chinese consumers with favorable attitudes of China’s domestic apparel brands tend to hold negative attitudes of counterfeit apparel products. Fifth and sixth, it was found that Chinese consumers with high level of face-saving values show positive attitudes of foreign (Western) apparel brands and counterfeit apparel products. Seventh, Chinese consumers with high level of face-saving values also possess strong materialistic values. Consequently Chinese consumers with strong materialistic values tend to hold positive attitudes of counterfeit apparel products and foreign (Western) apparel products, but negative attitudes of China’s domestic apparel brands. The findings of this study show that Chinese consumers have a very low level of perception about knowledge of counterfeit apparel products. It is necessary to connect educators, government, apparel industry, and brand owners to develop and enhance anti-counterfeit educational programs. These programs should clearly explain the perception about knowledge of Intellectual Property Rights (IPR), trademark, and the negative causes of counterfeit products are warranted. Also, it is better for China’s domestic apparel brand companies to develop better brand images and improve product quality to meet Chinese consumers’ face-saving standards and materialistic values.
Keywords: Criteria; Attitudes; Counterfeit; Face-saving; Ethical valuesChinese apparel purchasing